Training simulation with nothing but training data - simulating performance based on training data without the help of performance diagnostics in a laboratory - Ludwig, M.; Schaefer, D.; Asteroth, A. (Proceedings of the 4th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2016)
Analyzing training performance in sport is usually based on standardized test protocols and needs laboratory equipment, e.g., for measuring blood lactate concentration or other physiological body parameters. Avoiding special equipment and standardized test protocols, we show that it is possible to reach a quality of performance simulation comparable to the results of laboratory studies using training models with nothing but training data. For this purpose, we introduce a fitting concept for a performance model that takes the peculiarities of using training data for the task of performance diagnostics into account. With a specific way of data preprocessing, accuracy of laboratory studies can be achieved for about 50% of the tested subjects, while lower correlation of the other 50% can be explained.